An energy aware design flow of distributed industrial wireless sensor and actuator networks - Abrishambaf, Reza (2015)
Wireless Sensor Network (WSN) is an emerging technology which has been employed recently in various applications such as healthcare systems, environmental monitoring, military and industrial applications. This is due to the easy deployment and (re)configuration of the sensor nodes in the environment. It also has the potential of being integrated into the distributed manufacturing systems particularly when sensors and actuators are combined to form a wireless sensor and actuator network. IEC 61499 function block standard has been employed recently in order to model the distributed control systems. In this paper, an energy aware design flow and modeling approach for the development of industrial wireless sensor and actuator networks using IEC 61499 standard will be presented and by utilizing the Petri net as an analytical tool for event-based systems, the performance of the structural and behavioral models will be evaluated. Several factors such as reachability, coverability, transient and steady state analysis will be discussed in order to demonstrate the controllability of the proposed design flow.